Holocaust Emotion Cards: Project Presentation - Taczyńska, Katarzyna; Pałubicka, Kamila (Poznańskie Studia Slawistyczne, 2023)
The purpose of this article is to present the project Holocaust Emotion Cards, which was created as part of the course Innovation and Entrepreneurship for Holocaust Memory, run by Western Galilee College. In the first part of the presentation, we will present the assumptions and concepts of the project, as well as the process of creating the cards. In the second part, we will discuss the cards themselves and the way to use them in educational work.